Loss of Pax6 Causes Regional Changes in Dll1 Expression in Developing Cerebral Cortex - Dorà, Elena; Price, David J.; Mason, John O. (Frontiers in Cellular Neuroscience, 2019)
The transcription factor Pax6 controls multiple aspects of forebrain development. Conditional deletion of Pax6 in embryonic mouse cortex causes increased proliferation of cortical progenitor cells and a concomitant decrease in neural differentiation. Notch signalling is known to regulate the balance between proliferation and differentiation of cortical progenitor cells, suggesting a possible connection between Pax6 and Notch signalling. We investigated how expression of the Notch ligand delta-like 1 (Dll1) is altered by loss of Pax6. Acute cortex-specific deletion of Pax6 resulted in a widespread decrease in the density of Dll1+ cells at embryonic days 12.5 and 13.5 (E12.5 and E13.5). In constitutive loss-of-function mutants, decreases in the densities of Dll1+ cells were more limited both spatially and temporally. Controlled over-expression of Pax6 had no detectable effect on Dll1 expression. The proneural transcription factor Neurog2 is a known target of Pax6 that can activate Dll1 expression and we found clear co-expression of Neurog2 and Dll1 in radial glial progenitors, suggesting that Pax6’s effect on Dll1 could be mediated through Neurog2. However, we found no change in Dll1+ cells in Neurog2-/- cortex suggesting either that Neurog2 is not directly involved, or that its loss of function in embryonic cortex can be compensated for.